سورۃ آل عمران میں کتاب الجنائز سے متعلق فقہی احکام کا علمی جائزہ : تفسیر قرطبی کی روشنی میں: Scientific review of jurisprudence rulings related to Kitab al-Janaiz in Surah Al-Imran: In the light of Tafsir al-Qurtubi (Al-Aasar, 2025)
Death is an annihilation in which every soul descends, and it is a reality that cannot be denied, and it is a necessity that every religion, every race and every creature suffers from. Therefore, the rulings related to it are also necessary for every religion. Islam has also described detailed rules regarding funeral arrangements and cremation. In this paper, mainly the jurisprudential opinions of Imam Qurtubi have been scientifically evaluated, for which Surah Aal Imran has been selected from his jurisprudential commentary Al-Jami Lahkam al-Qur'an, which is the scope of this paper. Then these rulings are explained in the light of the Holy Quran, Ahadith Tayyaba and Islamic jurisprudence.